Shallot Compress on The Body Temperature of Baby Aged 0-12 Months Who Suffer AESI (Adverse Event of Special Interest) - Komalasari Komalasari; Hikmah Ifayanti (Universitas Aisyah Pringsewu, 2022)
In Indonesia, immunization is still a challenge. The proportion of children aged 12-23 months who have received all of their basic immunizations is remains low, at 57.9%. According to data from Lampung Province in 2018, 67.3 percent of children aged 12 to 23 months had received all of their baseline immunizations. Meanwhile, the proportion of complete basic immunization for infants in the South Lampung Regency in 2018 was still below the target, reaching 71.6%. The research objective was to determine the effectiveness of shallot compresses on the body temperature of babies aged 0-12 months who suffer AESI (Adverse Event of Special Interest). This type of research is a pre-experiment using one group pretest-posttest design. The sample in this research was babies aged 0-12 months who suffer post-immunization fever, with a sample of 17 respondents by using accidental sampling. In analysis used the T-test (paired sample t-test).The results of univariate analysis obtained that the average temperature of babies aged 0-12 months who suffer AESI before being given the shallot compress treatment was 38.1 ° C with a standard deviation of 0.295 and decreased after being given a shallot compress to 37.4 ° C with a standard deviation of 0.441. The results of the bivariate analysis showed the effect of shallot compresses on the body temperature of babies aged 0-12 months who experienced AESI (p-value = 0,000 (p-value less than 0.05). Suggestions for the health workers to be able to teach compresses with shallot in the intervention for managing hyperthermia in children after immunization. Abstrak: Pemberian imunisasi masih menjadi masalah di Indonesia. Proporsi imunisasi dasar lengkap pada anak umur 12-23 bulan masih rendah yakni 57,9 %. Data di Provinsi Lampung tahun 2018, proporsi imunisasi dasar lengkap pada anak umur 12-23 bulan mencapai 67,3%. Sedangkan proporsi imunisasi dasar lengkap pada bayi di Kabupaten Lampung Selatan tahun 2018 masih dibawah target yaitu mencapai 71,6%. Tujuan penelitian ini adalah mengetahui efektivitas kompres bawang merah terhadap suhu tubuh anak usia 0-12 bulan yang mengalami KIPI. Jenis penelitian ini praeksperiment dengan menggunakan rancangan one group pretest posttest. Sampel dalam penelitian ini adalah anak usia 0-12 bulan yang mengalami demam pasca imunisasi, dengan sampel sebanyak 17 responden, menggunakan accidental sampling. Analisis menggunakan uji T (paired sample t-test). Hasil analisis univariat diperoleh Rata-rata suhu anak usia 0-12 bulan yang mengalami KIPI sebelum diberi perlakuan kompres bawang merah yaitu 38,1 oC dengan standar deviasi 0,295 dan mengalami penurunan setelah diberi kompres bawang merah menjadi 37,4oC dengan standar deviasi 0,441. Hasil analisis bivariat diperoleh adanya pengaruh kompres bawang merah terhadap suhu tubuh anak usia 0-12 bulan yang mengalami KIPI (p-value= 0,000 (p-value kurang dari 0,05). Saran bagi petugas kesehatan untuk dapat mengajarkan kompres dengan bawang merah didalam intervensi penatalaksanaan hipertermi pada anak pasca imunisasi.